Modified chitosan composite material with self-assembly intercalation structure as well as preparation method and application of modified chitosan composite material

By combining the modified pussy soil with the carboxymethyling base shell polyose, a composite material with a self -assembly layer insertion structure is formed, and the problem of poorly dissolving the chitosan and the unsatisfactory antibacterial properties is solved, and efficient bacteriostatic and multifunctional are achieved Effect.

CN119367230APending Publication Date: 2025-01-28OPAL COSMETICS HUIZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411160629.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The poor solubility and poor antibacterial properties of chitosan limit their application in antibacterial materials.

Method used

By macro -wave treatment, heating treatment, and washing treatment of the puffed soil with the composite solution, it is prepared to modify the bentonic soil, and combine it with the carboxymethyling base shell polycan to form a composite material with a self -assembly layer insertion structure.

Benefits of technology

It improves the stability and antibacterial effect of materials, shows obvious bacteriostatic effects on Mara, E. coli, and Golden Poetlobacteria, and has the effects of reducing oil -controlled fluffy, relieving itching and relaxing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005006307680000051
    Figure BDA0005006307680000051
  • Figure BDA0005006307680000061
    Figure BDA0005006307680000061
  • Figure BDA0005006307680000091
    Figure BDA0005006307680000091
Patent Text Reader

Abstract

The invention belongs to the field of chitosan composite materials, and particularly relates to a modified chitosan composite material with a self-assembly intercalation structure as well as a preparation method and application of the modified chitosan composite material. The modified chitosan composite material with the self-assembly intercalation structure comprises a composite structure formed by modified bentonite and carboxymethyl chitosan, and the modified bentonite is prepared by mixing bentonite and a compound alcohol solution and then sequentially performing microwave treatment, heating treatment and water washing treatment. The modified chitosan composite material with the self-assembly intercalation structure has good stability, antibacterial effect, oil-controlling and fluffy effect, itching-relieving and soothing effect and irritation-reducing effect. The invention further provides a preparation method and application of the modified chitosan composite material with the self-assembly intercalation structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chitosan composite materials, and in particular relates to a modified chitosan composite material with a self-assembled layer-intercalation structure and a preparation method and application thereof. Background Art

[0002] In people's daily lives, bacteria and fungi are everywhere. Today's antibacterial ingredients include various antibiotics, metal ions and their oxides, various organic composite materials, etc. However, these antibacterial materials will have adverse effects on the human body after going through the ecological cycle. Therefore, in order to maintain human health and achieve antibacterial effects, it is very important to develop green, environmentally friendly, non-toxic and harmless antibacterial materials.

[0003] Chitosan, also known as deacetylated chitin, is obtained by deacetylation of chitin, which is widely present in nature. Its chemical name is polyglucosamine (1-4)-2-amino-BD glucose. Chitosan has good biocompatibility, biodegradability, no toxic side effects and antibacterial properties. In recent years, it has a wide range of application prospects in the fields of medicine and health care, food preservation, agriculture, and cosmetics. However, the solubility of high-purity chitosan in neutral solution is poor, and it cannot exert its antibacterial activity well, which limits the application of chitosan. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a modified chitosan composite material with a self-assembled intercalation structure, which can solve the problems of poor solubility of chitosan and unsatisfactory antibacterial performance; the modified chitosan composite material with a self-assembled intercalation structure of the present invention has good stability, antibacterial effect, oil control and fluffy effect, antipruritic and soothing effect, and irritation reduction effect. The present invention also provides a preparation method and application of the modified chitosan composite material with a self-assembled intercalation structure.

[0005] The technical solution adopted by the present invention to solve the above problems is as follows:

[0006] A modified chitosan composite material with a self-assembled intercalation structure comprises a composite structure formed by modified bentonite and carboxymethyl chitosan. The modified bentonite is prepared by mixing bentonite with a composite alcohol solution and then sequentially subjecting the mixture to microwave treatment, heating treatment and water washing treatment.

[0007] Furthermore, the fineness of the modified bentonite is 200-400 meshes.

[0008] Furthermore, the mass ratio of the modified bentonite to the carboxymethyl chitosan is 1:25-40.

[0009] Preferably, the mass ratio of the modified bentonite to the carboxymethyl chitosan is 32:1.

[0010] Furthermore, the fineness of the bentonite is 100-400 meshes.

[0011] Furthermore, the mass ratio of the bentonite to the composite alcohol solution is 1:2.5-4.

[0012] Furthermore, the composite alcohol solution comprises 0.5-1.2 wt % of a weak acid and 98.8-99.5 wt % of a solvent; the weak acid is at least one of citric acid, malic acid, and phosphoric acid; and the solvent is at least one of butanediol, propylene glycol, and glycerol.

[0013] Furthermore, the heat treatment is performed at a temperature of 250 to 350° C. for 150 to 250 minutes in an inert gas atmosphere.

[0014] Furthermore, the inert gas is at least one of nitrogen, argon and helium.

[0015] Furthermore, the power of the microwave treatment is 400-800W, and the time of the microwave treatment is 4-8min.

[0016] Furthermore, the water washing treatment is performed 2 to 6 times.

[0017] Furthermore, after the water washing process, a drying process and a grinding process are also included.

[0018] The present invention also provides a method for preparing the modified chitosan composite material having a self-assembled intercalation structure, comprising the following steps:

[0019] S1. The bentonite and the composite alcohol solution are mixed and then subjected to microwave treatment, heating treatment and water washing treatment to obtain modified bentonite;

[0020] S2. dissolving carboxymethyl chitosan in water to obtain a carboxymethyl chitosan solution;

[0021] S3. Mixing the carboxymethyl chitosan solution with the modified bentonite, stirring and defoaming the mixture, and filtering the mixture to obtain a modified chitosan composite material having a self-assembled layered intercalation structure.

[0022] Furthermore, in step S2, the concentration of the carboxymethyl chitosan solution is 12-18 wt%.

[0023] Preferably, in step S2, the concentration of the carboxymethyl chitosan solution is 16 wt %.

[0024] Furthermore, in step S2, the viscosity of the carboxymethyl chitosan solution is 20000-40000 cp.

[0025] Preferably, in step S2, the viscosity of the carboxymethyl chitosan solution is 30000 cp.

[0026] Furthermore, in step S3, the stirring temperature is 50-70° C., the stirring speed is 150-220 rpm, and the stirring time is 10-15 h.

[0027] Preferably, in step S3, the stirring time is 12 hours.

[0028] Furthermore, in step S3, the defoaming treatment is static defoaming treatment, ultrasonic defoaming treatment or defoaming treatment by adding a defoaming agent.

[0029] Furthermore, the ultrasonic power in the ultrasonic defoaming treatment is 300-800W, and the ultrasonic time is 20-40min.

[0030] Furthermore, the defoaming agent is at least one of polyvinyl alcohol, ceteth-10 phosphate, and ceteth-8 phosphate.

[0031] Furthermore, the amount of the defoaming agent added is 0.05-0.2% of the total mass of the carboxymethyl chitosan solution and the modified bentonite.

[0032] Furthermore, in step S3, the filtration is vacuum filtration, and the mesh size of the vacuum filtration is 200 to 400 meshes.

[0033] The present invention provides an application of the modified chitosan composite material with a self-assembled intercalation structure in the preparation of daily chemicals. In daily chemicals, the modified chitosan composite material with a self-assembled intercalation structure can play the role of oil control, fluffiness, antibacterial, anti-dandruff, anti-itching, repair or reduce the irritation of daily chemicals.

[0034] Furthermore, the modified chitosan composite material with a self-assembled layer intercalation structure is used to prepare daily chemicals with oil control, bulking, antibacterial, anti-dandruff, antipruritic, soothing or repairing effects.

[0035] The present invention has the following beneficial effects:

[0036] The present invention first pre-treats bentonite, and then microwaves the bentonite and a composite alcohol solution containing a weak acid, and then treats it at high temperature to obtain a modified bentonite, thereby increasing the internal spacing of the bentonite, so that carboxymethyl chitosan is more easily intercalated into the bentonite; at the same time, the modified bentonite can improve the dispersibility and hygroscopicity of the material, and the mass ratio between the modified bentonite and the carboxymethyl chitosan is adjusted to a suitable ratio, thereby improving the stability of the suspension, and solving the problem that the bentonite is insoluble in water and is easy to settle in the liquid. The modified chitosan composite material with a self-assembled layer intercalation structure of the present invention can also solve the problem that the solubility of chitosan is poor and the antibacterial performance is not ideal, and is a green antibacterial and environmentally friendly material, showing obvious antibacterial effects on Malassezia, Escherichia coli and Staphylococcus aureus; in addition, the modified chitosan composite material with a self-assembled layer intercalation structure of the present invention also has the effects of removing dandruff, controlling oil and fluffy, relieving itching and reducing the irritation of surfactants, and is suitable for application in the preparation of daily chemicals, and has a huge application potential in green cosmetics and a broad prospect.

[0037] The present invention applies and prepares chitosan and bentonite in the form of liquid, and is no longer limited to the powder or film prepared in previous studies. The application range of the material is expanded by the liquid form. The preparation method of the modified chitosan composite material with a self-assembled intercalation structure of the present invention is simple and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a sample picture of the modified chitosan composite material with a self-assembled layer-intercalation structure according to Example 1 of the present invention;

[0039] Figure 2 This is an electron microscope scanning image of the modified chitosan composite material with a self-assembled layer-intercalation structure according to Example 1 of the present invention;

[0040] Figure 3 This is an EDS elemental analysis diagram of the modified chitosan composite material with a self-assembled layer-intercalated structure according to Example 1 of the present invention;

[0041] Figure 4 This is the XRD diagram of the modified chitosan composite material with a self-assembled layer-intercalated structure in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are not limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Unless otherwise specified, the test materials, reagents, methods and equipment used in the following examples are conventional test materials, reagents, methods and equipment in the technical field; unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources. The following performance tests were all repeated three times, and the data are the average or average ± standard deviation of the three repeated experiments.

[0044] Examples 1 to 10 respectively provide a modified chitosan composite material having a self-assembled layer-intercalation structure, as follows:

[0045] Example 1 The preparation method of the modified chitosan composite material having a self-assembled intercalation structure is as follows:

[0046] S1. The bentonite passed through a 300-mesh sieve was mixed with a composite alcohol solution (0.8 wt% citric acid and 99.2 wt% butanediol) in a mass ratio of 1:3.2, placed in a 500 W microwave reactor for 6 min, filtered after completion, and the filter residue was placed in a tubular furnace, nitrogen was introduced, and heated at 300 ° C for 200 min. After heating, it was washed with water 4 times, dried and ground to obtain modified bentonite;

[0047] S2. Weigh 16 g of carboxymethyl chitosan and dissolve it in 84 mL of deionized water, stir until the carboxymethyl chitosan is completely dissolved to obtain a carboxymethyl chitosan solution having a concentration of 16 wt %; the viscosity of the carboxymethyl chitosan solution is 30000 cp;

[0048] S3. The modified bentonite obtained in step S1 is passed through a 300-mesh sieve to obtain modified bentonite powder, 0.5 g of the modified bentonite powder is weighed and added to the carboxymethyl chitosan solution obtained in step S2, and stirred at a speed of 200 rpm for 12 h in a water bath at 60° C. After stirring, defoaming treatment is performed with an ultrasonic power of 500 W for 30 min, and vacuum filtration is performed through a 300-mesh filter to obtain a modified chitosan composite material with a self-assembled layered structure.

[0049] Example 1: Sample of modified chitosan composite material with self-assembled intercalation structure Figure 1 As shown; Example 1 has a self-assembled layer structure of the modified chitosan composite material scanning electron microscope as shown Figure 2 Example 1: EDS elemental analysis of modified chitosan composite material with self-assembled intercalation structure Figure 3 As shown, Si and Al are the characteristic elements of bentonite. Figure 3 It can be seen that carboxymethyl chitosan is uniformly intercalated in the layered structure of bentonite; the XRD pattern of the modified chitosan composite material with self-assembled intercalated structure in Example 1 is as follows: Figure 4 As shown, from Figure 4 It can be seen that the peak position of bentonite (001) surface moves significantly after intercalation of carboxymethyl chitosan, which indicates that the interlayer spacing of bentonite increases and carboxymethyl chitosan is successfully intercalated.

[0050] The method for preparing a modified chitosan composite material having a self-assembled layered structure in Examples 2 to 8 is similar to that in Example 1, except that some parameters are different from those in Example 1. The parameters that are different between Examples 2 to 8 and Example 1 are shown in Table 1 below. Except for the different preparation parameters shown in Table 1, the remaining preparation parameters and preparation steps of Examples 2 to 8 are the same as those in Example 1.

[0051] Table 1:

[0052]

[0053]

[0054] Example 9 The preparation method of the modified chitosan composite material having a self-assembled layered intercalation structure is as follows:

[0055] S1. The bentonite passed through a 100 mesh sieve was mixed with a composite alcohol solution (1.2 wt% citric acid and 98.8 wt% propylene glycol) in a mass ratio of 1:2.5, placed in an 800 W microwave reactor for 4 min, filtered after completion, and the filter residue was placed in a tubular furnace, nitrogen was introduced, and heated at 250 ° C for 250 min. After heating, it was washed twice with water, dried and ground to obtain modified bentonite;

[0056] S2. Weigh 15 g of carboxymethyl chitosan and dissolve it in 85 mL of deionized water, stirring until the carboxymethyl chitosan is completely dissolved to obtain a carboxymethyl chitosan solution having a concentration of 15 wt %; the viscosity of the carboxymethyl chitosan solution is 28000 cp;

[0057] S3. The modified bentonite obtained in step S1 is passed through a 200-mesh sieve to obtain modified bentonite powder, 0.45 g of the modified bentonite powder is weighed and added to the carboxymethyl chitosan solution obtained in step S2, and stirred at a speed of 150 rpm for 10 h in a water bath at 70° C. After stirring, the carboxymethyl chitosan solution and 0.1 wt% of polyvinyl alcohol in the total mass of the modified bentonite are added as a defoaming agent for defoaming treatment, and a modified chitosan composite material with a self-assembled layered structure is obtained after vacuum filtration through a 200-mesh filter.

[0058] Example 10 The preparation method of the modified chitosan composite material having a self-assembled layered intercalation structure is as follows:

[0059] S1. The bentonite passed through a 400 mesh sieve was mixed with a composite alcohol solution (0.5wt% citric acid and 99.5wt% glycerol) in a mass ratio of 1:4, placed in a 400W microwave reactor for 8 minutes, filtered after completion, and the filter residue was placed in a tubular furnace, nitrogen was introduced, and heated at 350°C for 150 minutes. After heating, it was washed with water 6 times, and the modified bentonite was obtained after drying and grinding;

[0060] S2. Weigh 17 g of carboxymethyl chitosan and dissolve it in 83 mL of deionized water, stirring until the carboxymethyl chitosan is completely dissolved to obtain a carboxymethyl chitosan solution having a mass percentage concentration of 17%; the viscosity of the carboxymethyl chitosan solution is 34000 cp;

[0061] S3. The modified bentonite obtained in step S1 is passed through a 400-mesh sieve to obtain modified bentonite powder. 0.6 g of the modified bentonite powder is weighed and added to the carboxymethyl chitosan solution obtained in step S2. The solution is stirred at a speed of 220 rpm for 15 h in a water bath at 50°C. After stirring, the solution is allowed to stand for 24 h to defoam. The modified chitosan composite material having a self-assembled layered structure is obtained after vacuum filtration through a 400-mesh filter.

[0062] Comparative Example 1:

[0063] 16 g of carboxymethyl chitosan was weighed and dissolved in 100 mL of deionized water, and stirred until the carboxymethyl chitosan was completely dissolved to obtain a carboxymethyl chitosan solution.

[0064] Comparative Example 2:

[0065] 0.5 g of the modified bentonite powder prepared in Example 1 and passed through a 300-mesh sieve was added to 100 mL of deionized water and mixed evenly to obtain a bentonite material.

[0066] Comparative Example 3:

[0067] The difference from Example 1 is that 16 g of carboxymethyl chitosan in Example 1 is replaced by 16 g of succinyl carboxymethyl chitosan, and the remaining steps and parameters are the same as those in Example 1.

[0068] Comparative Example 4:

[0069] The difference from Example 1 is that 0.5 g of modified bentonite powder passing through a 300-mesh sieve in Example 1 is replaced by 0.8 g of modified bentonite powder passing through a 300-mesh sieve, and the remaining steps and parameters are the same as in Example 1.

[0070] Comparative Example 5:

[0071] The difference from Example 1 is that 0.5 g of modified bentonite powder passing through a 300-mesh sieve in Example 1 is replaced by 0.2 g of modified bentonite powder passing through a 300-mesh sieve, and the remaining steps and parameters are the same as in Example 1.

[0072] Comparative Example 6:

[0073] The difference from Example 1 is that 0.5 g of modified bentonite powder passing through a 300-mesh sieve in Example 1 is replaced by 0.5 g of modified bentonite powder passing through a 100-mesh sieve, and the remaining steps and parameters are the same as in Example 1.

[0074] Comparative Example 7:

[0075] (1) Weighing 16 g of carboxymethyl chitosan and dissolving it in 84 mL of deionized water, stirring until the carboxymethyl chitosan is completely dissolved, to obtain a carboxymethyl chitosan solution with a mass percentage concentration of 16%; the viscosity of the carboxymethyl chitosan solution is 30000 cp;

[0076] (2) 0.5 g of unmodified bentonite powder passed through a 300-mesh sieve was added to the carboxymethyl chitosan solution obtained in step (1), and the solution was stirred at a speed of 200 rpm for 12 h in a water bath at 60° C. After stirring, defoaming treatment was performed at a power of 500 W for 30 min, and a bentonite-chitosan composite material was obtained after vacuum filtration through a 300-mesh filter.

[0077] Comparative Example 8:

[0078] The difference from Example 1 is that the modification steps of bentonite are different. The preparation method of the modified bentonite of Comparative Example 8 is as follows: the bentonite through a 300-mesh sieve is mixed evenly with a composite alcohol solution (0.8 wt% citric acid and 99.2 wt% butanediol) in a mass ratio of 1:3.2, stirred at a speed of 200 rpm for 1 hour, filtered after completion, the filter residue is placed in a tubular furnace, nitrogen is introduced, and heated at a temperature of 300°C for 200 minutes. After heating, it is washed with water 4 times, and the modified bentonite is obtained after drying and grinding. The remaining steps and parameters are the same as those of Example 1.

[0079] Comparative Example 9:

[0080] The difference from Example 1 is that 0.8 wt % of citric acid in the composite alcohol solution of Example 1 is replaced by 0.8 wt % of sulfuric acid, and the remaining steps and parameters are the same as those of Example 1.

[0081] Comparative Example 10:

[0082] The difference from Example 1 is that the composite alcohol solution (0.8 wt % citric acid and 99.2 wt % butanediol) in Example 1 is replaced by 0.8 wt % citric acid and 99.2 wt % ethanol, and the remaining steps and parameters are the same as those in Example 1.

[0083] Comparative Example 11:

[0084] The difference from Example 1 is that the heating temperature of step (1) in Example 1 is changed from 300° C. to 150° C., and the remaining steps and parameters are the same as those in Example 1.

[0085] Comparative Example 12:

[0086] The difference from Example 1 is that step (1) of Example 1 is replaced by: the bentonite passed through a 200-mesh sieve is mixed evenly with a composite alcohol solution (0.8 wt% citric acid and 99.2 wt% butanediol) in a mass ratio of 1:3.2, and then placed in a 500 W microwave reactor for 6 min, filtered after the end, and the filter residue is washed with water 4 times, and dried to obtain modified bentonite. The remaining steps and parameters are the same as those in Example 1.

[0087] Comparative Example 13:

[0088] The difference from Example 1 is that: step (1) of Example 1 is replaced by: the bentonite passed through a 300-mesh sieve is mixed evenly with a composite alcohol solution (0.8 wt% citric acid and 99.2 wt% butanediol) in a mass ratio of 1:3.2, and then heated to reflux for 5 h at 80°C, filtered after the end, and the filter residue is placed in a tubular furnace, nitrogen is introduced, and heated at 300°C for 200 min. After the heating is completed, it is washed with water 4 times and dried to obtain modified bentonite. The remaining steps and parameters are the same as those in Example 1.

[0089] Performance Test:

[0090] The performance tests of the modified chitosan composite material with self-assembled intercalation structure prepared in the above examples and the product prepared in the comparative example are as follows:

[0091] 1. Stability test:

[0092] 15 mL of the final product obtained in Examples 1 to 10 and Comparative Examples 1 to 13 were taken as samples and placed in colorless transparent PE bottles. The PE bottles containing the test samples were placed at 25°C for 7 days, and then at 45°C for 7 days, and the steps were repeated once, and finally returned to room temperature to observe the room temperature stability and high temperature stability of the samples. The test results are shown in Table 2.

[0093] Table 2:

[0094]

[0095]

[0096] In Table 2, "passed" means that the appearance of the sample does not change after the stability test. From the test results in Table 2, it can be seen that the modified chitosan composite materials with self-assembled layer intercalation structure in the embodiments of the present invention have good stability. After being placed alternately at 25°C and 45°C for 4 weeks, the appearance of the samples of Examples 1 to 10 does not change.

[0097] In the sample of Comparative Example 2, only the modified bentonite is added, and carboxymethyl chitosan is not added, so the bentonite cannot be stably dispersed in the aqueous solution, and the final product has a stratification phenomenon. Comparative Example 3 changes the type of chitosan, but the compatibility of succinyl carboxymethyl chitosan and modified bentonite is poor, and succinyl carboxymethyl chitosan is difficult to be intercalated into the modified bentonite, resulting in a lower stability of the final product. In the sample of Comparative Example 4, compared with Example 1, the amount of bentonite added is too much, resulting in a reduced stability of the final product, and a large amount of bentonite is precipitated at the bottom of the PE bottle. In Comparative Example 6, the particles of bentonite are larger, resulting in a reduced suspension of bentonite, and carboxymethyl chitosan is difficult to be intercalated into bentonite, and the stability of the final product is poor. In Comparative Example 7, unmodified bentonite is mixed with a carboxymethyl chitosan solution, and the bentonite is unmodified, and its dispersibility and hygroscopicity are poor, so that the modified chitosan composite material finally prepared has poor stability. After being placed alternately at 25°C and 45°C for 4 weeks, the final products of Comparative Examples 8 to 13 all showed varying degrees of deterioration and poor stability, indicating that in the present invention, the modification process of bentonite affects its matching effect with carboxymethyl chitosan and affects the stability of the final product.

[0098] 2. Antibacterial performance test of Escherichia coli and Staphylococcus aureus:

[0099] The antibacterial properties of the final products of Examples 1 to 10 and Comparative Examples 1 to 13 were tested on an agar medium. Escherichia coli was used as the test strain, and a broth culture solution and an agar culture solution were prepared and sterilized with high pressure steam at 115°C. The strain was cultured with the broth medium, and the culture solution was washed with PBS buffer after culture. The OD value was measured by an ultraviolet spectrophotometer. 600 Detect the absorbance and adjust the concentration of the bacterial solution until the absorbance value is 0.4. The concentration of this bacterial solution is 10 7 CFU / mL, and then diluted to 10 with PBS. 5CFU / mL, this concentration of bacterial solution is used as the inhibition zone detection solution. Use a 1mL pipette to transfer the bacterial solution to the agar medium, and use a glass coating rod to evenly apply the bacterial solution to the entire medium. The entire operation is performed in a sterile sterilization table. The final products of Examples 1 to 10 and Comparative Examples 1 to 13 are diluted 10 times, gently pressed on the agar medium using an Oxford cup, and then the diluted suspension is dropped onto the medium, cultured at a constant temperature of 37°C for 24 hours, and then the size of the inhibition zone in the plate is measured. Each test sample was tested in parallel 3 times, and the test results were averaged. The test results are shown in Table 3.

[0100] Table 3:

[0101]

[0102]

[0103] It can be seen from Table 3 that the modified chitosan composite material with a self-assembled layer intercalation structure of the present invention has a good effect of inhibiting Escherichia coli and Staphylococcus aureus. The inhibition zones of the modified chitosan composite materials with a self-assembled layer intercalation structure of Examples 1 to 10 against Escherichia coli and Staphylococcus aureus are all above 10 mm.

[0104] 3. Malassezia antibacterial performance test / dandruff removal effect test:

[0105] The test method refers to QB / T2738-20237.3 Evaluation method for antibacterial and antimicrobial effects of daily chemical products. The strain used is Malassezia furfur ATCC44344, and the culture medium used is olive oil culture medium. The test results are shown in Table 4.

[0106] Table 4:

[0107] Group Antibacterial rate (%) Group Antibacterial rate (%) Example 1 99.82 Comparative Example 1 26.72 Example 2 98.61 Comparative Example 2 19.16 Example 3 99.08 Comparative Example 3 65.32 Example 4 98.92 Comparative Example 4 81.01 Example 5 97.35 Comparative Example 5 75.84 Example 6 98.61 Comparative Example 6 60.26 Example 7 97.73 Comparative Example 7 78.84 Example 8 99.02 Comparative Example 8 80.74 Example 9 95.31 Comparative Example 9 83.99 Example 10 97.15 Comparative Example 10 87.25 / / Comparative Example 11 82.26 / / Comparative Example 12 81.83 / / Comparative Example 13 80.63

[0108] The human scalp is colonized by a large number of microorganisms, including bacteria, fungi, viruses, parasites, etc. These microbial communities are important barriers to scalp health, and the frequent occurrence of scalp problems is related to factors such as scalp microbial flora imbalance. In a healthy and stable scalp, Malassezia (Malassezia furfur) exists as a scalp symbiotic bacterium. When dandruff occurs, the density of Malassezia on the scalp is 1.5 to 2 times that of normal conditions. The excessive proliferation of Malassezia will interfere with cell membrane signal transmission and damage cell membranes, which is intuitively manifested as an aggravated exfoliation process of the scalp stratum corneum, thereby causing dandruff.

[0109] From the results in Table 4, it can be seen that the modified chitosan composite material with a self-assembled layer intercalation structure of the present invention has a good inhibitory effect on Malassezia, and the inhibition rate of the modified chitosan composite material with a self-assembled layer intercalation structure of Examples 1 to 10 on Malassezia is above 95%. That is, the modified chitosan composite material with a self-assembled layer intercalation structure of the present invention also has a good anti-dandruff effect.

[0110] 4. Oil control and fluffy effect test:

[0111] In this test, human sebaceous gland cells SZ95 were selected to construct an in vitro acne model. The sebum secretion process of human skin was simulated by the oil secretion of SZ95 cells. The oil content of sebaceous gland cells was qualitatively and quantitatively detected by fluorescence quantitative method, so as to evaluate whether the test substance has the effect of oil control.

[0112] Test sample: the final products of Examples 1 to 10 and Comparative Examples 1 to 13, prepared into a solution with a mass concentration of 1% using H-DMEM culture medium (hereinafter referred to as culture medium) containing 10% FBS; positive control group: 500 μM minoxidil.

[0113] Test steps: SZ95 cells were cultured at 2×10 4 The number of cells was inoculated into a 24-well plate and cultured for 24 hours at 37°C, 5% CO2 and saturated humidity. After the culture was completed, the culture solution was discarded, 0.5 mL of culture solution was added to the blank control group, 0.5 mL of 10 μM testosterone culture solution, 0.5 mL of 10 μM testosterone sample solution, and 0.5 mL of 500 μM minoxidil culture solution were added to the model control group, the sample group to be tested, and the positive control group to induce modeling for 24 hours, and the culture solution was discarded, and 0.5 mL of PBS solution was added to each well for washing, followed by staining with 3 mM Nile red (source leaf biology) diluted with PBS, incubated at 37°C in the dark for 10 minutes, and washed with PBS. The fluorescence intensity of Nile red was detected by a multifunctional microplate reader with an excitation wavelength of 485 nm / emission wavelength of 565 nm, and the fluorescence gray value was converted by Image J to evaluate the relative fluorescence intensity of the blank control group, the model control group, the sample group to be tested, and the positive control group. The test results are shown in Table 5.

[0114] Table 5:

[0115]

[0116]

[0117] As shown in Table 5, after adding testosterone culture medium to the model control group, the oil secretion of the cells increased, and the fluorescence intensity of the model control group was significantly enhanced compared with the blank control group; and after adding 500 μM minoxidil culture medium to the positive control group, the oil secretion of the cells was inhibited, and the fluorescence intensity was significantly reduced. After using the samples of the embodiments of the present invention, the fluorescence intensity of the cells was significantly reduced, and the fluorescence intensity of some embodiments was even lower than that of the positive control group, indicating that the modified chitosan composite material with a self-assembled layer intercalation structure of the present invention can inhibit oil secretion and has a good oil control effect. On the other hand, due to the reduction of scalp oil secretion, the hair becomes refreshing, non-sticky, fluffy and light.

[0118] 5. Anti-itch and anti-redness performance test:

[0119] Test principle: Histamine is mainly present in mast cells and basophils. When the body is stimulated, the cells degranulate and release histamine. Histamine can stimulate C-fiber terminal-related receptors to produce itching and pain. This test uses histamine to build a model on the skin surface, then applies the test sample, and volunteers score the itching degree of the modeled area before and after using the sample to determine the antipruritic and soothing effect of the test sample.

[0120] Test sample: The final products of Examples 1 to 10 and Comparative Examples 1 to 13 were prepared into a solution with a mass concentration of 1% with deionized water, and deionized water was used as a blank control group.

[0121] Test steps: 120 volunteers with healthy skin and no damage on the inner side of their arms were selected. The inner side of the left and right forearms were used as test areas. A total of 240 test areas were randomly divided into 24 groups, with 10 test areas in each group, and one test sample was used. After sticking high-viscosity and low-sensitivity tape on the test area 5 times (reducing the thickness of the adult stratum corneum to simulate the thickness of infant skin), a non-woven fabric soaked in histamine aqueous solution (10 mg / mL) was applied for 10 minutes. After removing the film cloth, it was wiped clean with clean water. The volunteers scored the itching degree of the modeling area, and then applied the test sample. The itching score of the test area was evaluated 20 minutes after use. The change rate of the itching score before and after the use of the test sample was compared to evaluate the anti-itching and soothing effect of the test sample.

[0122] The test scoring criteria are shown in Table 6.

[0123] Table 6:

[0124]

[0125] Itch score change rate (%) = (itch score after use - itch score before use) / itch score before use × 100%

[0126] The test results are shown in Table 7.

[0127] Table 7:

[0128] Group Change rate of pruritus score (%) Group Change rate of pruritus score (%) Blank control group -5.6 Comparative Example 1 -13.5 Example 1 -41.2 Comparative Example 2 -6.6 Example 2 -38.8 Comparative Example 3 -21.8 Example 3 -40.6 Comparative Example 4 -32.4 Example 4 -38.6 Comparative Example 5 -20.5 Example 5 -35.1 Comparative Example 6 -28.3 Example 6 -40.3 Comparative Example 7 -22.6 Example 7 -36.5 Comparative Example 8 -24.0 Example 8 -41.0 Comparative Example 9 -26.8 Example 9 -37.4 Comparative Example 10 -25.5 Example 10 -35.2 Comparative Example 11 -30.8 / / Comparative Example 12 -28.6 / / Comparative Example 13 -31.1

[0129] It can be seen from the test results in Table 7 that after using the modified chitosan composite materials with a self-assembled layered intercalation structure of Examples 1 to 10 of the present invention, the itching scores of the volunteers were significantly reduced, and the reduction in the itching scores was much greater than that of the blank control group and the comparative example, indicating that the modified chitosan composite materials with a self-assembled layered intercalation structure of the present invention can play a significant antipruritic and soothing effect.

[0130] 6. Synergistic reduction of irritation performance test:

[0131] This test uses the zein method to test the irritation of the surfactant system.

[0132] Test principle: Zein is almost completely insoluble in water, but its water solubility increases after interacting with surfactants; stronger irritating surfactants tend to dissolve zein more easily than weaker irritating surfactants. Therefore, according to the change in nitrogen content before and after the action of surfactants in aqueous solution, the solubility of zein after the action of surfactants can be determined, and the nitrogen content in the dissolved zein is proportional to the skin irritation caused by surfactants, which can be used to judge the irritation of surfactants.

[0133] The irritation index was determined by the zein method according to the following literature: Dong Yinmao, Si Xiaofan, Peng Jinluan. Testing the irritation of surfactants using zein[J]. Surfactant Chemical Industry, 2002, 32(5): 59-61.

[0134] Test sample: Final products of Examples 1 to 10 and Comparative Examples 1 to 13

[0135] Test steps: Using 0.3% SDS (sodium dodecyl sulfate) aqueous solution as the control group, the zein value of 1% test sample in 0.3% SDS aqueous solution was examined.

[0136] The test results are shown in Table 8.

[0137] Table 8:

[0138]

[0139]

[0140] From the test results in Table 8, it can be seen that the zein value of the 0.3% SDS aqueous solution is 5.72, and after the test sample is added to the system, the zein value of the system decreases to varying degrees, indicating that the samples of the embodiments of the present invention and the comparative examples have different degrees of effect in reducing the irritation of the surfactant. From the test data of the comparative examples, it can be seen that the zein value of the embodiments is reduced to a greater extent, which indicates that compared with the final product prepared in the comparative example, the modified chitosan composite material with a self-assembled layer intercalation structure of the embodiments of the present invention has a better effect in reducing irritation.

[0141] It can be seen from the test results of Tables 2 to 7 that the antibacterial effect, inhibitory effect on Malassezia, oil control and fluffy effect, antipruritic and soothing effect, and irritation reduction effect of the modified chitosan composite material with a self-assembled layer intercalation structure in the embodiments of the present invention are all better than the final products of Comparative Examples 1 to 13.

[0142] From the comparative test results of the embodiment and comparative examples 1 and 2, it can be seen that there is a synergistic effect between carboxymethyl chitosan and modified bentonite. After the modified bentonite is intercalated with carboxymethyl chitosan, the antibacterial effect, the inhibitory effect on Malassezia, the oil control and fluffy effect, the antipruritic and soothing effect, and the irritation reduction effect of the final product are all enhanced. If only carboxymethyl chitosan or modified bentonite is used as the antibacterial material, the various effects of the final product will deteriorate.

[0143] From the comparative test results of the embodiment and comparative example 3, it can be seen that the specific type of chitosan selected will also affect the antibacterial effect of the final product, the inhibitory effect on Malassezia, the oil control and fluffy effect, the antipruritic and soothing effect, and the effect of reducing irritation. The present invention prefers carboxymethyl chitosan.

[0144] From the comparative test results of the embodiment and comparative examples 4 and 5, it can be seen that the addition amount of modified bentonite affects the interlayer structure of the modified chitosan composite material, thereby affecting the various properties of the final product. The mass ratio of modified bentonite to carboxymethyl chitosan in the present invention is preferably 1:25-40. Within this range, the final product has good antibacterial effect, inhibitory effect on Malassezia, oil control and fluffy effect, antipruritic and soothing effect, and irritation reduction effect.

[0145] From the comparative test results of the embodiment and comparative example 6, it can be seen that the fineness of the modified bentonite affects the interlayer structure of the modified chitosan composite material, thereby affecting the various properties of the final product. The fineness of the modified bentonite in the present invention is preferably 200-400 mesh. Within this range, the final product has good antibacterial effect, inhibitory effect on Malassezia, oil control and fluffy effect, antipruritic and soothing effect, and irritation reduction effect.

[0146] From the comparative test results of the embodiment and comparative examples 7 to 13, it can be seen that whether the bentonite is modified, the type of weak acid in the composite alcohol solution during the modification process, the type of solvent in the composite alcohol solution, the operating steps during the modification process, the temperature, etc., all have an impact on the various properties of the final material.

[0147] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0148] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0149] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A modified chitosan composite material with a self-assembled intercalation structure, characterized in that: The invention comprises a composite structure formed by modified bentonite and carboxymethyl chitosan. The modified bentonite is prepared by mixing bentonite with a composite alcohol solution and then sequentially subjecting the mixture to microwave treatment, heating treatment and water washing treatment.

2. The modified chitosan composite material with a self-assembled intercalation structure according to claim 1, characterized in that: The modified bentonite has a fineness of 200-400 meshes.

3. The modified chitosan composite material with a self-assembled intercalation structure according to claim 1, characterized in that: The mass ratio of the modified bentonite to the carboxymethyl chitosan is 1:25-40.

4. The modified chitosan composite material with a self-assembled intercalation structure according to claim 1, characterized in that: The composite alcohol solution comprises 0.5-1.2 wt % of a weak acid and 98.8-99.5 wt % of a solvent; the weak acid is at least one of citric acid, malic acid and phosphoric acid; and the solvent is at least one of butanediol, propylene glycol and glycerol.

5. The modified chitosan composite material with a self-assembled intercalation structure according to claim 1, characterized in that: The bentonite has a fineness of 100 to 400 meshes.

6. The modified chitosan composite material with a self-assembled intercalation structure according to claim 1, characterized in that: The mass ratio of the bentonite to the composite alcohol solution is 1:2.5-4.

7. The modified chitosan composite material with a self-assembled intercalation structure according to claim 1, characterized in that: The heating treatment is heating at a temperature of 250-350° C. for 150-250 min in an inert gas atmosphere; the power of the microwave treatment is 400-800 W, and the time of the microwave treatment is 4-8 min.

8. A method for preparing a modified chitosan composite material having a self-assembled intercalation structure according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. The bentonite and the composite alcohol solution are mixed and then subjected to microwave treatment, heating treatment and water washing treatment to obtain modified bentonite; S2. dissolving carboxymethyl chitosan in water to obtain a carboxymethyl chitosan solution; S3. Mixing the carboxymethyl chitosan solution with the modified bentonite, stirring and defoaming the mixture, and filtering the mixture to obtain a modified chitosan composite material having a self-assembled layered intercalation structure.

9. Use of the modified chitosan composite material with a self-assembled intercalation structure according to any one of claims 1 to 7 in the preparation of daily chemicals.

10. Use of the modified chitosan composite material with a self-assembled intercalation structure according to claim 9 in the preparation of daily chemicals, characterized in that: The modified chitosan composite material with a self-assembled intercalation structure is used to prepare daily chemicals with oil control, bulking, antibacterial, anti-dandruff, antipruritic, soothing or repairing effects.